STRATEGI PEMBINAAN KARAKTER SISWA DI SEKOLAH DASAR ISLAM TERPADU BUAH HATI PEMALANG - Rhisty Frida Utami; Soegito Soegito; Muhdi Muhdi (Jurnal Manajemen Pendidikan (JMP), 2016)
The focus of this research is how the implementation of the Strategic Plan for Character Development in Students Primary Islam School (SDIT) Buah Hati Pemalang based plan strategy through planning, organizing, implementation and evaluation of character building program. The approach used in this research is descriptive qualitative. This research was conducted in SDIT Buah Hati Pemalang. Source of data derived from the principal, classroom teachers, subject teachers, school committee, Tsamrotul Fuad Foundation, students, and parents.The results showed the program in SDIT Buah Hati Pemalang in character building of students based on the Quran and hadith outlined in the flagship program of the Islamic and 10 competencies Muslim personality of children that have Aqidah clean, worship properly, have good morals, to have independence, broad-minded, has a strong physical, spirited opportunities, regular in all matters, to appreciate the time, beneficial for others. SDIT Buah Hati Pemalang has had a strategic plan in the program character building of students by implementing a strategy of SBM include the bases of school management based on the principle promote transparency and accountability, for enhancing the character of students is done in an open, transparent, systematic, consistent, and sustainable decision-making according to ability, the condition of the school.Based on the findings above, it is recommended that school principals supported the teachers there are synergistic cooperation to related institutions/ organizations in order to expedite and facilitate the performance especially in the procurement of character building program. Suggested classroom teachers, subject teachers and classroom teachers collaborate and work together in providing educational services to students in the form of learning and mentoring students in learning.